Accurate DOA Estimations Using Microstrip Adaptive Arrays in the Presence of Mutual Coupling Effect. (24th November 2013) - Huang, Qiulin; Zhou, Hongxing; Bao, Jianhui; Shi, Xiaowei
Abstract : A new mutual coupling calibration method is proposed for adaptive antenna arrays and is employed in the DOA estimations to calibrate the received signals. The new method is developed via the transformation between the embedded element patterns and the isolated element patterns. The new method is characterized by the wide adaptability of element structures such as dipole arrays and microstrip arrays. Additionally, the new method is suitable not only for the linear polarization but also for the circular polarization. It is shown that accurate calibration of the mutual coupling can be obtained for the incident signals in the 3 dB beam width and the wider angle range, and, consequently, accurate [1D] and [2D] DOA estimations can be obtained. Effectiveness of the new calibration method is verified by a linearly polarized microstrip ULA, a circularly polarized microstrip ULA, and a circularly polarized microstrip UCA.